OPTIMISASI PARAMETER SUPPORT VECTOR MACHINE DENGAN PARTICLE SWARM OPTIMIZATION UNTUK PENINGKATAN KLASIFIKASI DIABETES - Maulana, Muhammad Reza; Sucipto, Adi; Mulyo, Harminto Mulyo (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This research explores the effectiveness of using Particle Swarm Optimization (PSO) to optimize Support Vector Machine (SVM) parameters in diabetes diagnosis. Using Kaggle's